Risk factors and neonatal outcome in preterm births: A hospital-based case-control study - Shrestha, Sabita; Joshi, Rakshya; Pandey, Jyoti; Chaudhary, Jully; Prasad Singh, Jaya (Journal of Chitwan Medical College, 2025)
Introduction: Preterm birth is the delivery before 37 completed weeks of gestation. Prematurity is the leading cause of neonatal mortality globally. This study aims to determine the risk factors and neonatal outcomes of preterm birth. Method: A case-control study was conducted in the department of Obstetrics and Gynaecology, Chitwan Medical College Teaching Hospital, Nepal, from December 2020 to November 2021. A total of 175 women who delivered between 28-37 weeks were taken as cases and 175 women who delivered at or beyond 37 weeks were included as controls. A structured proforma was used to collect relevant information like sociodemographic factors, past and present obstetric history, maternal physiological parameters and neonatal outcome. Data analysis was performed using IBM SPSS Statistics. The chi-square test (ꭓ2) was used to show the relationship between various risk factors and preterm birth. An odds ratio with a 95% confidence interval was estimated. Result: The mean gestational age of cases and controls was 34.44±2.06 and 39.00 1.20 weeks respectively. The major maternal risk factors of preterm birth were hypertensive disorder of pregnancy, pre-labour rupture of membrane, urinary tract infection in pregnancy, anaemia, and abnormal liquor volume. The mean weight of preterm and term neonates was 2111.9±573.86gm and 2938.3±479.63gm respectively. Preterm neonates had a significantly increased rate of NICU admission and requirement for respiratory support and phototherapy. Conclusion: The study establishes an association between maternal hypertensive disorder, pre-labour rupture of membrane, anaemia and preterm birth. Neonates of preterm gestational age are at increased morbidities.